2011
DOI: 10.1097/jom.0b013e31820061d7
|View full text |Cite
|
Sign up to set email alerts
|

Why are Financial Incentives not Effective at Influencing Some Smokers to Quit? Results of a Process Evaluation of a Worksite Trial Assessing the Efficacy of Financial Incentives for Smoking Cessation

Abstract: Financial incentives are ineffective at motivating some smokers to quit. Internal motivation and readiness to quit need to be sufficiently high for relatively modest incentives to be effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 17 publications
2
32
0
1
Order By: Relevance
“…This was linked to beliefs about smoking . Smokers described the health and social benefits of smoking: Enjoyment [29,35,36], stress reduction or relaxation [35,36], contact with friends and co-workers [29] and concerns about weight gain were they to stop [33,36]. Many non-smokers reported disliking smoking; but there were also smokers and non-smokers who felt there was no problem with smoking either at work or elsewhere [30,37].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was linked to beliefs about smoking . Smokers described the health and social benefits of smoking: Enjoyment [29,35,36], stress reduction or relaxation [35,36], contact with friends and co-workers [29] and concerns about weight gain were they to stop [33,36]. Many non-smokers reported disliking smoking; but there were also smokers and non-smokers who felt there was no problem with smoking either at work or elsewhere [30,37].…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies using employee interviews, focus groups, discussion board posts or surveys reported that participants found it helpful when their employer was clearly supportive of either smoking restrictions or interventions [26,29,31,34]. Employers could also be supportive by simply making participatory interventions available, thus offering their employees an opportunity to access a programme [26,35,38,39]. The issue could be different when the intervention was a workplace restriction or ban.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conducting smoking cessation interventions in the workplaces, including recruitment and regular follow-ups is necessary, given the high smoking rate among the workers; but also feasible as they work together and spend most of their daily time in their workplace [14]. Previous studies have suggested the efficacy of smoking cessation interventions in the workplace [15][16][17][18][19]. Several intervention approaches have shown to be effective for tobacco control including individual or group counselling, pharmacotherapy, and incentives.…”
Section: Introductionmentioning
confidence: 99%
“…Several intervention approaches have shown to be effective for tobacco control including individual or group counselling, pharmacotherapy, and incentives. However, these approaches are often used in developed countries [15][16][17]. In developing countries, approaches such as environmental support or self-help interventions were often reported, which were however shown to be less effective [18,19].…”
Section: Introductionmentioning
confidence: 99%